Investigating the application of skate-secured 3-D accelerometers to assess on-ice performance and the associated relationships with off-ice performance metrics in competitive youth hockey athletes - Twible, B.; Dalton, B.; McNeil, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The ability to rapidly generate muscle force (produce power) is a critical determinant of athletic performance. Recent technological progress provides opportunities for limb-specific assessment of neuromuscular parameters during training or competition, which can reveal inter-limb asymmetries (ILAs) that may limit functional capacity. Yet, due to difficulties with on-ice data collection, hockey athletes are an understudied population compared to other sporting groups. The purpose of this study was to explore the implementation of skate-secured 3-D accelerometers to assess on-ice performance, and to investigate the relationship between onand off-ice performance metrics. We hypothesized that relationships would exist between on- and off-ice metrics, including ILAs, and that lower-limb ILA would be inversely related to skating performance. METHODS: Seventeen participants (15.0 ± 1.2 years; seven females) completed two performance-based tasks to assess lower-limb function: a 30-m forward sprint (on-ice), and a vertical countermovement jump (CMJ) (off-ice). On-ice metrics of interest included mean stride power and total sprint time. The vertical CMJ was performed on a dual force plate system, and metrics of interest included peak jump height, relative peak force and power, relative braking rate of force development, and impulse (braking and propulsive). Mean stride power, as well as CMJ impulse (braking and propulsive), force, and rate of force development were used to assess ILA. Linear regressions were performed to determine relationships between on- and off-ice variables. RESULTS: An inverse relationship was found for mean stride power and skating sprint time (R2 = 0.30; p = 0.02). Positive relationships were detected between peak CMJ height and both mean stride power (R2 = 0.37; p = 0.01) and skating sprint time (R2 = 0.75; p < 0.01), as well as between peak CMJ relative power and both mean stride power (R2 = 0.30; p = 0.02) and skating sprint time (R2 = 0.71; p < 0.01). Regarding asymmetries, there was a positive relationship between ILAs for CMJ rate of force development and mean stride power (R2 = 0.31; p = 0.02); however, no other relationships between off-ice and on-ice ILA measures were significant (p * 0.32). Additionally, no on- or off-ice measure of ILA related to skating sprint time (p * 0.09). CONCLUSION: In summary, skate-secured 3-D accelerometers allow assessment of limb-specific on-ice parameters that are important for skating performance. Although a relationship between on- and off-ice performance was identified, the presence of on- or off-ice ILAs may not be important for short-term power production.